IMA Commission on New Minerals, Nomenclature and Classification (CNMNC), Newsletter 53: IMA No. 2019-085 - Biglia, Marco Esteban (2020)
Liraite NaCa2Mn2+ 2 [Fe3+Fe2+]Mn2+ 2 (PO4)6(H2O)2 Ceferino Namuncurá pegmatite, Pocho Department, Córdoba Province, Argentina (31◦370 4500 S, 65◦150 0300 W)